BISMILLAH, SAYA MENIKAH Studi Kasus Pembentukan Keluarga pada Pasangan Mahasiswa - Alfaruqy, Muhammad Zulfa (Al-Qalb : Jurnal Psikologi Islam, 2019)
Every human being has a requirement to overcome loneliness. In accordance with the theory of early adult development, one of the ways to against it is to build a family. But, couples who did it while just a college student has a complex challenge, especially if deciding taaruf because of religious rules that prohibit relationships before marriage. The aim of this research is to understand the psychological dynamics of college students in building a family through the taaruf process.This research uses the qualitative method with a case study approach. Researchers involve two subjects of college students who have been married. Data collection was done by interview, observation, and focus group discussion. Couples who build a family by taaruf process, through four stages, there are understanding relations concept, introductions, taaruf, and marriage. They made the interaction in line with Islamic rules that do not allow courtship. The introduction made only a remote view. During the process of taaruf, there is no direct communication to avoid romantic shade. The wedding process becomes an important epiphany in life. Marriage is perceived as a social support that positively affects academic responsibility. Taaruf may be an alternative choice to avoid relationship which is not appropriate with religious rules. College students who decide to build a family, especially through the taaruf process, need to ensure their readiness in academic responsibility.